2007
DOI: 10.1186/bcr1639
|View full text |Cite
|
Sign up to set email alerts
|

Hormone receptor status, tumor characteristics, and prognosis: a prospective cohort of breast cancer patients

Abstract: BackgroundBreast cancer patients with tumors that are estrogen receptor (ER)-positive and/or progesterone receptor (PR)-positive have lower risks of mortality after their diagnosis compared to women with ER- and/or PR-negative disease. However, few studies have evaluated variations in the risks of breast cancer-specific mortality across ER/PR status by either demographic or clinical characteristics.MethodsUsing data from 11 population-based cancer registries that participate in the SEER (Surveillance, Epidemio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

29
480
3
17

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 651 publications
(529 citation statements)
references
References 30 publications
29
480
3
17
Order By: Relevance
“…This is especially true for ER/PgR data. The cancer registries that participate in the Surveillance, Epidemiology, and End Results programme of the U.S. National Cancer Institute began collecting data on ER/PgR status of breast cancer in 1990, and only in 2001 did the proportion of cases with no recorded information decrease to less than 20% [25]. The result obtained for the present study, 24% of cases in the final analysis, is acceptable.…”
Section: Discussionmentioning
confidence: 55%
“…This is especially true for ER/PgR data. The cancer registries that participate in the Surveillance, Epidemiology, and End Results programme of the U.S. National Cancer Institute began collecting data on ER/PgR status of breast cancer in 1990, and only in 2001 did the proportion of cases with no recorded information decrease to less than 20% [25]. The result obtained for the present study, 24% of cases in the final analysis, is acceptable.…”
Section: Discussionmentioning
confidence: 55%
“…It has been shown that different hormone receptor status could have an effect on the level of breast cancer patient's mortality (Dunnwald et al, 2007). We found majority of patients, 63% were hormone receptor positive (ER/PR+) and only 6.6% were identified as triple negative.…”
Section: Discussionmentioning
confidence: 67%
“…[12] Because it represents a rare receptor subtype, it is unlikely that a prospective clinical trial would ever be conducted to define the optimal adjuvant treatment strategy for this disease. ER negative/PR positive status may arise from testing artifacts, including false positive IHC results in a truly HR negative tumor [20] …”
Section: Discussionmentioning
confidence: 99%
“…[12] Some data suggests that cancers may not significantly benefit from adjuvant endocrine therapy. [1].…”
mentioning
confidence: 99%